Geography for Nongeographers - Spellman, Frank R. (Government Institutes, 2010)
Geography is a multidisciplinary field which looks at both physical and social aspects of the world. The broad scope of the field makes it a daunting area for those who do not have a specific background in it. Geography for Non-Geographers thus introduces readers to the most important aspects of geography and how they affect us. It covers all areas of geography, from physical geography to climate and weather to human and cultural geography. Geography for Non-Geographers is presented in an accessible and straightforward manner, explaining scientific concepts in the most basic way possible. Along with basic geographical principles, the text provides a clear, concise presentation of the consequences of the physical interactions with the environment we inhabit. Each chapter ends with a chapter review test to help evaluate mastery of the concepts presented. Readers acquire an understanding of and skill in geographical principles, adding a critical component to their professional knowledge.